Desquamative gingivitis mimicking mild gingivitis - Yajamanya, Shravanthi Raghav (J Indian Soc Periodontol, 2016)
The aim of this report is to diagnose the cause for episodic, shifting type of mild inflammation in the isolated areas of gingiva noted by the patient for 1 year. A 33-year-old female patient presented with a chief complaint of mild pain and occasional burning sensation confined to the gingiva to the Department of Periodontology and Oral Implantology. Clinical presentation of the gingiva was seen to mimic mild form of gingivitis for 1 year, with no noted systemic involvement gingival biopsy was performed. The presence of Tzanck cell was noted along with intraepithelial split pointing toward pemphigus. Thus, the study concludes that thorough and meticulous gingival examination can reveal the picture of underlying systemic alterations and is the key for early diagnosis and prompt treatment.